2017
DOI: 10.1038/srep43897
|View full text |Cite
|
Sign up to set email alerts
|

RUG3 and ATM synergistically regulate the alternative splicing of mitochondrial nad2 and the DNA damage response in Arabidopsis thaliana

Abstract: The root apical meristem (RAM) determines both RAM activity and the growth of roots. Plant roots are constantly exposed to adverse environmental stresses that can cause DNA damage or cell cycle arrest in the RAM; however, the mechanism linking root meristematic activity and RAM size to the DNA damage response (DDR) is unclear. Here, we demonstrate that a loss of function in RCC1/UVR8/GEF-Like 3 (RUG3) substantially augmented the DDR and produced a cell cycle arrest in the RAM in rug3 mutant, leading to root gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…A plethora of retrograde signalling routes have been described ( de Souza et al ., ), however, and further studies will be needed to determine how they are connected to the DDR. Recently, in Arabidopsis, it was shown that the N‐terminal of ATM interacts with RUG3, a mitochondria protein, and that this interaction occurs within organelles, possibly to control the organelle DDR (Su et al ., ). In line with these findings, we observed that DDR components are required for plant tolerance to organelle DNA damage.…”
Section: Discussionmentioning
confidence: 97%
“…A plethora of retrograde signalling routes have been described ( de Souza et al ., ), however, and further studies will be needed to determine how they are connected to the DDR. Recently, in Arabidopsis, it was shown that the N‐terminal of ATM interacts with RUG3, a mitochondria protein, and that this interaction occurs within organelles, possibly to control the organelle DDR (Su et al ., ). In line with these findings, we observed that DDR components are required for plant tolerance to organelle DNA damage.…”
Section: Discussionmentioning
confidence: 97%
“…Other proteins that influence the splicing of group II introns in plant organelles include pentatricopeptide repeat (PPR) proteins, chloroplast RNA maturation (CRM)-related factors (i.e., the mCSF1 protein), members of the plant organellar RNA recognition (PORR) family, mitochondrial transcription termination factor (mTERF) related proteins and several other factors, which are seemingly unique to eukaryotes and are thus expected to evolve from the host genomes to function in organellar group II intron splicing in plants (reviewed in, e.g., [ 12 , 14 , 15 , 30 ]). Some of the proteins, such as nMAT2 [ 33 ], PMH2 [ 37 ] and mCSF1 [ 40 ], are required for the processing of a larger set of introns, while other factors such as PPR proteins (see, e.g., [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]) and mTERF15 [ 50 ] appear to be more specific, influencing the splicing of a single or only a few group II introns [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-mRNA splicing produces extensive proteomic and regulatory diversity during development. Accurate modulation of pre-mRNA splicing is essential for normal cellular functions in wheat, rice, and Arabidopsis (Fang et al 2017;Xia et al 2017;Marquez et al 2012;Su et al 2017). In plants, approximately 20% of the genes have multiple isoforms of transcripts that play various role in photosynthesis, disease resistance, flowering, quality, and other physiology processes (Wang et al 2006;Barbazuk et al 2008;Reddy 2007;Sestili et al 2015).…”
Section: Discussionmentioning
confidence: 99%